Business communication and emotional intelligence: Two sides of the same coin - Oliveira, Adilson Vagner de; Costa, Ana Paula Duarte; Ribeiro, Bruno Esquer; Silva, Josenilda Maria da (Seven Editora, 2023)
This article aims to investigate the mechanisms of business communication and its relations with the principles of emotional intelligence in the workplace. The survey was conducted in the municipality of Tangará da Serra-MT between the years 2022 and 2023, with a total of 724 workers from local commerce and service companies. In methodological terms, the investigation is characterized by a quantitative approach based on random collection of statistical data, with explanatory objectives regarding the phenomenon of communication in the professional environment. The results indicate the importance of developing the socio-emotional competencies present in the concept of emotional intelligence, focusing on the dynamics of business communication in order to allow the creation of healthy environments of interaction and cooperation. In addition, the research reinforces the evidence that most communication problems are related to the lack of emotional control of employees and their managers. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-115